Mercury exposure and short-term consequences on physiology and reproduction in Antarctic petrels - Carravieri, Alice; Fort, Jérôme; Tarroux, Arnaud; Cherel, Yves; Love, Oliver P.; Prieur, Solène; Brault-Favrou, Maud; Bustamante, Paco; Descamps, Sébastien (Environmental pollution (1987), 2018)
Mercury (Hg) is a pervasive contaminant reaching Antarctic environments through atmospheric transport and deposition. Seabirds as meso to top predators can accumulate high quantities of Hg through diet. Reproduction is one of the most sensitive endpoints of Hg toxicity in marine birds. Yet, few studies have explored Hg exposure and effects in Antarctic seabirds, where increasing environmental perturbations challenge animal populations. This study focuses on the Antarctic petrel Thalassoica antarctica from Svarthamaren, Antarctica, where the world's largest breeding population is thought to be in decline. Hg and the stable isotopes of carbon (δ13C, proxy of feeding habitat) and nitrogen (δ15N, trophic position/diet) were measured in red blood cells from 266 individuals over two breeding years (2012–13, 2013–14). Our aims were to 1) quantify the influence of individual traits (size and sex) and feeding ecology (foraging location, δ13C and δ15N values) on Hg exposure, and 2) test the relationship between Hg concentrations with body condition and breeding output (hatching success and chick survival). Hg concentrations in Antarctic petrels (mean ± SD, 0.84 ± 0.25, min-max, 0.42–2.71 μg g−1 dw) were relatively low when compared to other Antarctic seabirds. Hg concentrations increased significantly with δ15N values, indicating that individuals with a higher trophic level (i.e. feeding more on fish) had higher Hg exposure. By contrast, Hg exposure was not driven by feeding habitat (inferred from both foraging location and δ13C values), suggesting that Hg transfer to predators in Antarctic waters is relatively homogeneous over a large geographical scale. Hg concentrations were not related to body condition, hatching date and short-term breeding output. At present, Hg exposure is likely not of concern for this population. Nevertheless, further studies on other fitness parameters and long-term breeding output are warranted because Hg can have long-term population-level effects without consequences on current breeding success. [Display omitted] •Blood Hg concentrations were measured in a large sample of adult Antarctic petrels.•We assessed the influence of individual traits and feeding ecology on Hg exposure.•Hg exposure was low and dependent on trophic position.•Hatching date, success, and chick survival were not related to Hg burdens in parents.•Assessment of Hg correlates with other fitness traits and over the long-term is warranted. Blood Hg concentrations in Antarctic petrels were driven by trophic position and were not related to short-term breeding output.